Pre-contact Indigenous fire stewardship: a research framework and application to a Pacific Northwest temperate rainforest - Coughlan, Michael R.; Johnston, James D.; Derr, Kelly M.; Lewis, David G.; Johnson, Bart R. (Frontiers in Environmental Archaeology, 2024)
Fire is a key disturbance process that shapes the structure and function of montane temperate rainforest in the Pacific Northwest (PNW). Recent research is revealing more frequent historical fire activity in the western central Cascades than expected by conventional theory. Indigenous peoples have lived in the PNW for millennia. However, Indigenous people's roles in shaping vegetation mosaics in montane temperate forests of the PNW has been overlooked, despite archaeological evidence of long-term, continuous human use of these landscapes. In this paper, we present a generalizable research framework for overcoming biases often inherent in historical fire research. The framework centers Indigenous perspectives and ethnohistory, leveraging theory in human ecology and archaeology to interpret fire histories. We apply this framework to place-based, empirical evidence of Indigenous land use and dendroecological fire history. Our framework leads us to conclude that the most parsimonious explanation for the occurrence of historical high fire frequency in the western Cascades is Indigenous fire stewardship. Further, our case study makes apparent that scholars can no longer ignore the role of Indigenous people in driving montane forest dynamics in the PNW.